2019
DOI: 10.3201/eid2507.190301
|View full text |Cite
|
Sign up to set email alerts
|

Increased Threat of Urban Malaria from Anopheles stephensi Mosquitoes, Africa

Abstract: Malaria continues to be a major health threat in Africa, mainly in rural areas. Recently, the urban malaria vector Anopheles stephensi invaded Djibouti and Ethiopia, potentially spreading to other areas of Africa. Urgent action is needed to prevent urban malaria epidemics from emerging and causing a public health disaster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 9 publications
0
72
0
2
Order By: Relevance
“…coluzzii and An. funestus being the predominant malaria vector species [4]. However, some minor species are also cause for concern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…coluzzii and An. funestus being the predominant malaria vector species [4]. However, some minor species are also cause for concern.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the Asian native mosquito An. stephensi is now established in Ethiopia [4] and An. arabiensis is deemed a major cause of residual malaria transmission due to the species' insecticide avoidance behaviours [2].…”
Section: Introductionmentioning
confidence: 99%
“…Many important mosquito species contribute to parasite transmission, increasing the complexity of both surveillance and control efforts. Our focus is Anopheles stephensi, the Indian malaria mosquito, an aggressive malaria vector mosquito that has invaded and become established in Sri Lanka, Djibouti, and Ethiopia, with significant risk for range expansion into Somalia, Eritrea and Sudan (Faulde et al, 2014;Surendran et al, 2018;Seyfarth et al, 2019;Takken and Lindsay, 2019). In Djibouti, A. stephensi has been linked to a resurgence of severe infection with the human malaria parasite Plasmodium falciparum (Seyfarth et al, 2019), so increased focus on this species is relevant and timely for control.…”
Section: Introductionmentioning
confidence: 99%
“…The current presence and the possible spread of An. stephensi to African countries poses a potential health risk since it is a malaria vector well adapted to urban centers and it could cause malaria outbreaks of unprecedented sizes (Balkew et al, 2019;Takken and Lindsay, 2019). Our model indicates that the breadth of temperature range for An.…”
Section: Discussionmentioning
confidence: 91%
“…stephensi is a native mosquito of Asia (Sinka et al, 2010), recent research has reported that An. stephensi mosquitoes are already present in Africa, for example in Djibouti (Faulde et al, 2014), Ethiopia (Balkew et al, 2019;Carter et al, 2018), Sudan, and probably in neighboring countries (Takken and Lindsay, 2019;World Health Organization, 2019). The current presence and the possible spread of An.…”
Section: Discussionmentioning
confidence: 99%